Deconvolution of Mass Gain and Mass Loss Mechanisms During Carbothermic Reduction to Nitridation of Zirconia. Issue 5 (22nd February 2016) - Parkison, Adam J.; Nelson, Andrew T.
Abstract : A novel approach was used to understand the effects of processing conditions on the conversion of zirconium dioxide to zirconium carbonitride using a carbothermic reduction to nitridation process. The conversion process was studied through the use of thermogravimetric analysis, X‐ray diffraction (XRD), and scanning electron microscopy, resulting in an understanding of the nature and progression of conversion. The rate of mass change as measured through thermogravimetric analysis was plotted as a function of reaction progression, guiding the use of XRD in further understanding the conversion process. This approach was then used to characterize the important effect of initial compact morphology on conversion. Coupled analysis techniques allow for advancement of a number of hypotheses regarding the rate‐limiting factors along the various steps in the carbothermic reduction to nitridation process. These results demonstrate the value of the proposed approach to aid in deconstruction of competing reaction mechanisms as necessary to understand the system studied here or other systems of scientific and industrial relevance.